Mineral Nutrient Acquisition by Cotton Cultivars Grown Under Salt Stress - Özyiğit, İbrahim İlker; Doğan, İlhan; Doğan, İlhan; Demir, Göksel; Yalçın, İbrahim Ertuğrul (Taylor and Francis Ltd., 2017)
Physiological responses were investigated in two cotton cultivars grown at various concentrations of sodium chloride (NaCl) in order to determine the degree of the tolerance of the cultivars to salt stress and understand the physiological responses with respect to utilization of mineral nutrients. After germination of the seeds of cotton cultivars, they were transferred into standard pots with 210 g sterilized compost and watered with 30 ml Hoagland’s solution containing different concentrations (0, 50, 100, 200, and 400 mM) of NaCl at two-day intervals for 3 months. Growth parameters were measured and the mineral nutrient analyses were done using inductively coupled plasma optical emission spectrometry (ICP-OES, Thermo Fisher Scientific, Waltman, MA). It was observed that plant growth and mineral nutritional status of both cultivars were altered extensively in those grown with NaCl. Excess NaCl reduces the concentrations of certain mineral nutrients and increases that of others, the patterns depending on the mineral nutrient and the plant part and varieties being compared to the control.
Keywords: Gossypium hirsutum L.; Cotton; Mineral nutrition; Salinity stress